Investigate the effect of ortopedic metal artefact reduction algorithm on dosimetry of imrt prostate with hip prosthesis - Zakir, Nurul Najah Mohd (Universiti Sains Malaysia, 2025)
Prostate cancer is one of the most common cancers among Malaysian men, and radiotherapy—especially intensity-modulated radiation therapy (IMRT)—is a key treatment. However, metal hip implants in some patients can cause artefacts in computed tomography (CT) images, which affect the accuracy of anatomy and radiation dose calculations. This study investigated the efficiency of the Orthopedic Metal Artifact Reduction (OMAR) algorithm by Philips reduces these artefacts and improves dose accuracy in prostate IMRT. A custom male pelvic phantom with a metal hip implant was created using tissue-like materials and treated with a 6 MV photon beam. The radiation doses were calculated using the Eclipse treatment planning system (TPS) and checked using a calibrated thermoluminescent dosimeter (TLD) type 100. The results showed that OMAR significantly reduced image distortion and improved the accuracy of structure outlines and dose delivery. Treatment plans based on OMAR-corrected images had better dose conformity and uniformity. Statistical tests confirmed significant improvements in dose accuracy (p > 0.05) in several organs. Hence, the OMAR algorithm has been proven that it improve both image quality and radiation dose accuracy, making it a valuable tool for radiotherapy planning in patients with metal implants.